Cytokines and Chemokines as Regulators of Skeletal Muscle Inflammation: Presenting the Case of Duchenne Muscular Dystrophy - Boel De Paepe; Jan L. De Bleecker (Mediators of Inflammation)
Duchenne muscular dystrophy is a severe inherited muscle disease that affects 1 in 3500 boys worldwide. Infiltration of skeletal muscle by inflammatory cells is an important facet of disease pathophysiology and is strongly associated with disease severity in the individual patient. In the chronic inflammation that characterizes Duchenne muscle, cytokines and chemokines are considered essential activators and recruiters of inflammatory cells. In addition, they provide potential beneficiary effects on muscle fiber damage control and tissue regeneration. In this review, current knowledge of cytokine and chemokine expression in Duchenne muscular dystrophy and its relevant animal disease models is listed, and implications for future therapeutic avenues are discussed.